Effects of Laughter on Self-Report and Psychophysiological Measures of Stress - (:unkn) unknown (My University, 2017)
The purpose of this study was to investigate the relationship between laughter and stress reduction. Past research indicates that humor is related to stress reduction, but little is known about the specific role of laughter. It was hypothesized that laughter would have a similar effect. Stress was elicited through a mental arithmetic task, which was followed by a viewing of either a laughter-inducing video or a control (nature) video. Stress levels were assessed with both self-report and psychophysiological measures, including heart rate and respiration rate. Data was analyzed using one-within and one-between repeated measures ANOVAs. It was found that there were no significant between-group differences in physiological measures of stress. In both conditions, heart rate significantly increased during the arithmetic task, and significantly decreased during the video. Self-reported ratings of stress were significantly higher after the arithmetic task than they were following the video. The laughter group reported significantly lower feelings of self-reported stress, however, the laughter group also had significantly lower baseline measures of self-reported stress. As such, it was concluded that there were no significant effects of laughter on stress reduction.
Keywords: Heart Rate; Laughter; Stress; Stress Reduction